Impact of the Alexander technique on well‐being: a randomised controlled trial involving older adults with visual impairment. (1st February 2017) - Gleeson, Michael; Sherrington, Catherine; Lo, Serigne; Auld, Robin; Keay, Lisa
Abstract : Background: Older adults with visual loss have high rates of depression, restricted participation and reduced quality of life. We sought to measure the impact of lessons in the Alexander technique on vision‐related emotional and social well‐being, as secondary outcomes to a study on improving physical functioning in this population. Methods: This is a single‐blind randomised controlled trial. One hundred and twenty community‐dwelling adults aged 50 to 90 years with visual impairments were randomised to either 12 Alexander lessons over 12 weeks and usual care or usual care. The Perceived Visual Ability Scale, the Keele Assessment of Participation, the emotional subscale of the Impact of Vision Impairment Profile, the Positive and Negative Affect Scale and the five‐item Geriatric Depression Scale were administered at baseline and three and 12 months. Participants were receiving services from Guide Dogs NSW/ACT. Results: None of the validated questionnaires found statistically significant improvements after adjustment for baseline at three or 12 months, although the emotional subscale of the Impact of Vision Impairment approached significance in favour of the intervention group (4.54 points, 95 per cent CI: −0.14 to 9.21, p = 0.06). Depressive symptoms were prevalent and associated with greater impact of visual impairment on emotional well‐being (odds ratio: 1.12, 95 per cent CI: 1.07 to 1.17, p < 0.0001). Faster gait, an indicator of general mobility, was associated with less depressive symptoms (odds ratio: 1.27, 95 per cent CI: 1.06 to 1.54, p = 0.01). Conclusion: On average, there was no significant impact of weekly lessons in the Alexander technique on social and emotional well‐being, although the emotional impact of visual impairment showed a trend toward less distress in the intervention group. Our data found that emotional distress associated with visual impairment influences depressive symptoms but contrary to expectations, the level of social support received was not significant. Additionally, gait speed is a significant predictor of depressive symptoms, suggesting that general mobility is of importance to the well‐being of older adults with visual impairments.